The prolonged effect of film mulch and P application on lucerne forage yield in a semiarid environment - Kong, Meng; Gu, Yan-Jie; Han, Cheng-Long; Shi, Xiao-Peng; Kang, Jing; Siddique, Kadambot H. M.; Li, Feng-Min; Yuan, Zi-Qiang (Frontiers in Plant Science, 2023)
Introduction Limited water and soil phosphorus (P) availability often hampers lucerne productivity in semiarid regions. Plastic film mulch and P application typically enhance young lucerne (2–3 years) productivity by increasing soil water use and P availability. However, the prolonged impact of film mulch and P application on lucerne productivity as the stand ages remains unclear. Methods This study conducted a 9-year field experiment on the semiarid Loess Plateau to investigate how film mulch and P application affect lucerne forage yield, soil water content, and soil fertility. The field experiment used a split-plot design with randomized blocks, in which the whole plots were with (M1) and without plastic film mulch (M0), and the split plots were four P rates (0 (P0), 9.7 (P1), 19.2 (P2), and 28.8 (P3) kg P ha−1). Results and discussion The M1 treatment produced significantly higher lucerne forage yields than the M0 treatment during the first five years, but the yield-increasing effect of film mulch gradually diminished over time, with no effect in Years 6–8, and lower yields than the M0 treatment in Year 9. Phosphorus fertilization significantly increased forage yield after Year 3 in the M0 treatment, but only in Years 3–5 in the M1 treatment. In Years 2–5, film mulch significantly increased soil organic carbon, total nitrogen (N), inorganic N, and microbial biomass carbon in P0, P1, and P2 but not in P3. However, in Years 7–9, film mulch significantly decreased soil available potassium (K), organic carbon mineralization, lucerne density, and shoot K concentration, but did not reduce soil N and P availability at any level P of application. Moreover, plastic film mulch significantly increased the soil water content at 0–300 cm deep from Year 7 onwards. In conclusion, film mulch ceased to enhance lucerne production beyond year 6, which could not be attributed to soil water content, N or P availability but was partially associated with reduced soil K availability. Consequently, future research should focus on soil K availability, and K addition should be considered after five years in lucerne pastures mulched with plastic film in semiarid areas.